Role of Biofilm Formation in Mediation of Drug Resistance in E. Coli - Sila Imtiaz, Sidrah Saleem, Irfan Ahmad, Muhammad Imran, Sahar Imtiaz, Saadia Ch, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: Measure biofilm formation in clinical isolates of Escherichia coli and compare the survival of bacteria by treatment of ciprofloxacin, ceftriaxone and amoxicillin/clavulanic acid in the presence and absence of biofilm formation. Methodology: A total of ninety isolates of Escherichia coli were included in the study. All isolates were identified for biofilm production by microtiter assay. Antibiotic susceptibility test for all E. coli strains along with ATCC E. coli 25922 as a control was performed by agar dilution method (CLSI 2016) using three antibiotics e.g. ciprofloxacin, ceftriaxone and amoxicillin/clavulanic acid Result: Out of ninety E. coli isolates, 18(20%) were strong biofilm formers, 54(60%) were moderate and non-biofilm formers were 18(20%). Resistance to ciprofloxacin, ceftriaxone and amoxicillin/clavulanic acid were 75.5%, 63.3% and 22.2% respectively in all tested isolates. The rate of antibiotic resistance of strong biofilm formers, moderate formers and non-biofilm formers were 83.3%, 74% and 77.7% respectively for ciprofloxacin. Similarly, for ceftriaxone resistance pattern of strong, moderate and non-biofilm former were 66.6%, 66.6% and 50% respectively. Strong, moderate and non-biofilm forming E. coli were 11.1%, 27.7% and 22% respectively resistant to amoxicillin/clavulanic acid. Conclusion: Biofilm is not essentially involved in mediating drug resistance in E. coli against tested ciprofloxacin, ceftriaxone and amoxicillin/clavulanic acid. Biofilm formers showed more resistance to antibiotics than non-biofilm formers but statistical analysis of both groups against three antibiotics showed that there was no significant difference of resistance observed among them. There may be another molecular and enzymatic mechanism that allows bacteria to mediate resistance.